Molecular architecture and oligomerization of Candida glabrata Cdc13 underpin its telomeric DNA-binding and unfolding activity. Issue 2 (11th January 2023) - Coloma, Javier; Gonzalez-Rodriguez, Nayim; Balaguer, Francisco A; Gmurczyk, Karolina; Aicart-Ramos, Clara; Nuero, Óscar M; Luque-Ortega, Juan Román; Calugaru, Kimberly; Lue, Neal F; Moreno-Herrero, Fernando; Llorca, Oscar
Abstract: The CST complex is a key player in telomere replication and stability, which in yeast comprises Cdc13, Stn1 and Ten1. While Stn1 and Ten1 are very well conserved across species, Cdc13 does not resemble its mammalian counterpart CTC1 either in sequence or domain organization, and Cdc13 but not CTC1 displays functions independently of the rest of CST. Whereas the structures of human CTC1 and CST have been determined, the molecular organization of Cdc13 remains poorly understood. Here, we dissect the molecular architecture of Candida glabrata Cdc13 and show how it regulates binding to telomeric sequences. Cdc13 forms dimers through the interaction between OB-fold 2 (OB2) domains. Dimerization stimulates binding of OB3 to telomeric sequences, resulting in the unfolding of ssDNA secondary structure. Once bound to DNA, Cdc13 prevents the refolding of ssDNA by mechanisms involving all domains. OB1 also oligomerizes, inducing higher-order complexes of Cdc13 in vitro . OB1 truncation disrupts these complexes, affects ssDNA unfolding and reduces telomere length in C. glabrata . Together, our results reveal the molecular organization of C. glabrata Cdc13 and how this regulates the binding and the structure of DNA, and suggest that yeast species evolved distinct architectures of Cdc13 that share some common principles.